Differentiation between ovarian metastasis from colorectal carcinoma and primary ovarian carcinoma: Evaluation of tumour markers and "mille-feuille sign" on computed tomography/magnetic resonance imaging. Issue 124 (March 2020) - Kurokawa, Ryo; Nakai, Yudai; Gonoi, Wataru; Mori, Harushi; Tsuruga, Tetsushi; Makise, Naohiro; Ushiku, Tetsuo; Abe, Osamu
Highlights: "Mille-feuille sign" indicates ovarian metastasis from colorectal carcinoma. "Solid and cystic" morphology indicates primary ovarian carcinoma. Cancer antigen 125 was significantly higher in the primary ovarian carcinoma group. Carcinoembryonic antigen was significantly higher in the metastases group. Combining serum tumor markers and morphology improves the diagnostic ability. Abstract: Purpose: The purpose of this retrospective study was to evaluate the usefulness of serum tumour markers and morphological characteristics in CT/MRI to differentiate between ovarian metastases from colorectal carcinomas (OMCRC) and primary ovarian carcinomas (POC). Method: Preoperative radiological images of 41 OMCRCs from 27 patients (mean age ± SD: 52.2 ± 10.7 years) and 46 POCs from 36 patients (52.1 ± 12.7 years) were included. Three blinded gynecological radiologists classified tumour morphology into 'mille-feuille sign', 'solid and cystic', 'multicystic without nodules', and 'multicystic with nodules' groups and analysed using Fisher's exact test. Serum carcinoembryonic antigen (CEA), cancer antigen 125 (CA125), and carbohydrate antigen 19-9 levels were compared by Wilcoxon rank-sum test. Results: 'Mille-feuille sign' indicated OMCRC (OMCRC: 8/41, POC: 1/46, specificity = 0.98, p = 0.011) and had excellent interobserver agreement (Fleiss's kappa value = 0.96). 'Solid and cystic' indicated POC (18/41 vs 41/45, p < 0.001) and 'multicystic without nodules' indicated OMCRC (8/41 vs 2/46, p = 0.041). There was no significant difference in 'multicystic with nodules'. CA125 levels were higher in POCs (292.5 U/mL vs. 41.0 U/mL, p = 0.003). CEA levels were higher in OMCRCs (24.5 ng/mL vs 2 ng/mL, p < 0.001). CEA (< 6.3 ng/mL) AND (CA125 (≥87.0 U/mL) OR 'solid and cystic') indicated POC with high accuracy (3/41 vs 44/46, accuracy = 0.94, p < 0.001). Conclusions: Our new method with morphological classification and tumour markers were useful for differentiating the two tumours. In particular, the 'mille-feuille sign' frequently indicated OMCRC with high specificity and excellent interobserver agreement.